Faktor-Faktor yang Berhubungan dengan Perilaku Kader dalam Pencegahan Penularan Covid-19 Saat Kegiatan Posyandu Balita di Kota Pekanbaru - Winda Enjelika Enjelika; Ganis Indriati; Riri Novayelinda (Jurnal Vokasi Keperawatan (JVK), 2022)
The COVID-19 pandemic has disrupted the implementation of the integrated healthcare center. cadre behavior in preventing COVID-19 transmission When integrated healthcare center activities are needed so that integrated healthcare center activities continue to run according to health protocols. Methods:This type of research is quantitative using a descriptive correlation research design and a cross sectional approach. The sampling technique was purposive sampling as many as 76 respondents. The analysis used was bivariate analysis with chi square test. Results: The results showed that predisposing factors related to cadre behavior were knowledge (p value = 0.000) and attitudes (p value = 0.003) while the unrelated factor was culture (p value = 0.365). The enabling behavior of cadres in preventing COVID-19 transmission during integrated healthcare center activities for toddlers is the availability of facilities and infrastructure (p value = 0.002), while the unrelated factor is access to integrated healthcare centers (p value = 0.942). The reinforcement related to the behavior of cadres was the support of health workers (p value = 0.005) while unrelated was the support of community leaders (p value = 0.443). Conclusion: Based on the results of this study, it was concluded that knowledge, attitudes, availability of facilities and infrastructure and support of health workers were related to cadre behavior, while habits, access to posyandu and support from community leaders were not related to cadre behavior.